Lithium ion battery positive electrode composite material, preparation method thereof, positive plate and battery

By covering the surface of the positive electrode material of the lithium-ion battery with electron-rich organic matter and metal compounds to form stable Li-X or M-X ion bonds, the problem of easy corrosion of the cladding layer is solved and the structural stability and electrochemical performance of the positive electrode composite material of the lithium-ion battery are improved.

CN120389000APending Publication Date: 2025-07-29JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510405101.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-07-29

AI Technical Summary

Technical Problem

The cladding layer of the positive electrode material of the existing lithium-ion battery is easily corroded by the electrolyte during the cycle, resulting in low bonding strength and affecting electrochemical performance.

Method used

Organic substances and metal compounds containing electron-rich groups are used as coating agents to combine with the positive electrode material of lithium-ion battery through ion bonds to form stable Li-X or M-X ion bonds, thereby improving the bonding strength and stability of the coating layer.

Benefits of technology

The structural stability and electrochemical performance of the positive electrode composite material of lithium-ion battery are enhanced, and the cycle stability and first-time Coulomb efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120389000A_ABST
    Figure CN120389000A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion battery positive electrode composite material and a preparation method thereof, a positive electrode plate and a battery. The lithium ion battery positive electrode composite material comprises a lithium ion battery positive electrode material and a coating layer coating at least part of the surface of the lithium ion battery positive electrode material, a coating agent for forming the coating layer comprises an organic matter containing an electron-rich group, wherein the electron-rich group comprises at least one of-OH,-COO-,-F,-Cl,-Br,-I,-SO4 or-SO3; the electron-rich group is suitable for being combined with a Li element or a non-Li metal element in the positive electrode material of the lithium ion battery through an ionic bond. The positive plate comprises the positive electrode composite material. The battery comprises the positive plate. According to the positive electrode composite material provided by the invention, the problem of relatively low bonding strength of the current positive electrode material and the coating layer can be relieved, the bonding stability of the positive electrode material and the coating layer can be improved, and the electrochemical performance of the positive electrode composite material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular, to a composite cathode material for a lithium-ion battery, a preparation method thereof, a cathode sheet, and a battery. Background Art

[0002] With the popularization of electric vehicles, lithium-ion power batteries have advantages such as high energy density, environmental friendliness, and low energy consumption, so their market demand is increasing. However, there are many problems to be solved in lithium-ion batteries, such as poor cycle stability of the battery, poor thermal stability of materials, interfacial side reactions, and gas generation. As one of the main materials of the battery, the cathode material (cathode active material) affects the performance of the battery such as cycle stability. In actual production, the cathode material needs to avoid contact with water as much as possible, mainly because the LiO4 tetrahedron in the cathode material has strong polarity, and it is extremely easy to migrate when encountering water, resulting in the destruction of the layered structure. Therefore, effective technical means are needed to modify the cathode material.

[0003] At present, the effective modification methods for lithium-ion battery cathode materials mainly include doping and coating. Among them, doping can improve the capacity and structural stability of the material, and inhibit the phase change of the structure and material rupture during the cycle. Coating can physically block the material and the electrolyte, passivate the surface of the cathode material, and inhibit the side reaction with the electrolyte. Currently, the commonly used coating reagents are mainly electrochemically inert metal oxides and fast ion conductor solid electrolytes. However, the coating layers of these substances are easily corroded and damaged by the electrolyte during the cycle, and cannot provide lasting protection for the cathode material matrix. After long cycles, a passivation layer that is not easy to conduct electrons and ions will also be generated on the surface of the cathode material, resulting in a rapid decline in capacity.

[0004] Therefore, in order to improve the electrochemical performance stability of the battery, it is necessary to further develop more effective coated cathode materials and their preparation methods. Summary of the Invention

[0005] In view of this, the present invention aims to solve at least one of the technical problems in the related art to some extent. For this reason, the present invention provides a composite cathode material for a lithium-ion battery, a preparation method thereof, a cathode sheet, and a battery, which are beneficial to improving the binding stability of the lithium-ion battery cathode material and the coating layer, and further improving the electrochemical performance of the composite cathode material for a lithium-ion battery.

[0006] To solve the above technical problems, the present application is implemented as follows:

[0007] According to the first aspect of the present application, the present application provides a composite cathode material for a lithium-ion battery, the composite cathode material for a lithium-ion battery includes a lithium-ion battery cathode material and a coating layer coated on at least a part of the surface of the lithium-ion battery cathode material;

[0008] The coating agent used to form the coating layer includes organic substances containing electron-rich groups, where the electron-rich groups include at least one of -OH, -COO - , -F, -Cl, -Br, -I, -SO4 or -SO3; the electron-rich groups are suitable for binding with Li elements or non-Li metal elements in the cathode material of the lithium-ion battery through ionic bonds.

[0009] In some embodiments thereof, the non-Li metal elements include at least one of Ni, Co, Fe, Mn, Zn, Mg, Cu, Al, Ti, Zr, Na or K.

[0010] In some embodiments thereof, the organic substances containing electron-rich groups include at least one of ethyl fluoroacetate, methyl difluoroacetate, isopropyl trifluoroacetate, butyl fluoroacetate, tetradecyl fluoride, chlorotetradecane, bromotetradecane, tetradecanedioic acid, tetradecanol, sodium tetradecylsulfonate, isopropylsulfonyl chloride, sodium polystyrenesulfonate, dipropylene glycol butyl ether, polypropylene oxide, sodium polyacrylate, methoxypolyethylene glycol, brominated epoxy resin, brominated polystyrene, 5-sulfosalicylic acid, sodium sulfosalicylate, maleic acid mono-2-(methacryloyloxy)ethyl ester, ethoxylated castor oil glycolate, polyoxyethylene lauryl ether, sodium benzenesulfonate, sodium riboflavin phosphate, polyethylene glycol, stearic acid, butyl stearate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium dodecylsulfonate or sodium tetradecylsulfonate.

[0011] In some embodiments thereof, the coating agent further includes a metal compound.

[0012] In some embodiments thereof, the metal compound includes at least one of Al2O3, TiO2, LiPO3, LATP, LLZO, LLTO, AlPO4 or Zr3(PO4)4.

[0013] In some embodiments thereof, the thickness of the coating layer is 5 nm to 20 nm.

[0014] According to the second aspect of the present application, the present application provides a method for preparing a composite cathode material for a lithium-ion battery, the method comprising the following steps:

[0015] Provide a cathode material solution for a lithium-ion battery and a coating agent solution respectively;

[0016] Mix the cathode material solution for the lithium-ion battery and the coating agent solution, and obtain a coated matrix material after reaction;

[0017] Sinter the coated matrix material to obtain the composite cathode material for the lithium-ion battery;

[0018] The positive electrode composite material of the lithium ion battery includes a positive electrode material of the lithium ion battery and a coating layer coated on at least a part of the surface of the positive electrode material of the lithium ion battery;

[0019] The coating agent in the coating agent solution includes an organic compound containing an electron-rich group, where the electron-rich group includes at least one of -OH, -COO - , -F, -Cl, -Br, -I, -SO4 or -SO3; the electron-rich group is suitable for binding to the Li element or non-Li metal element in the positive electrode material of the lithium ion battery through an ionic bond.

[0020] In some embodiments, the positive electrode material of the lithium ion battery in the positive electrode material solution of the lithium ion battery includes Li a M b P c O d , where M includes at least one of non-Li metal elements, 1 ≤ a ≤ 1.3, 0 < b ≤ 2, 0 ≤ c ≤ 1, 0 < d ≤ 4.

[0021] In some embodiments, the M includes at least one of Ni, Co, Fe, Mn, Zn, Mg, Cu, Al, Ti, Zr, Na or K.

[0022] In some embodiments, the solvent in the positive electrode material solution of the lithium ion battery includes at least one of water, methanol, ethanol, acetone, N-methylpyrrolidone, ethylene glycol, glycerol, pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or N,N-diethylformamide.

[0023] In some embodiments, the organic compound containing an electron-rich group includes at least one of ethyl fluoroacetate, methyl difluoroacetate, isopropyl trifluoroacetate, butyl fluoroacetate, tetradecyl fluoride, chlorotetradecane, bromotetradecane, tetradecanedioic acid, tetradecanol, sodium tetradecylsulfonate, isopropylsulfonyl chloride, sodium polystyrenesulfonate, dipropylene glycol butyl ether, polypropylene oxide, sodium polyacrylate, methoxypolyethylene glycol, brominated epoxy resin, brominated polystyrene, 5-sulfosalicylic acid, sodium sulfosalicylate, maleic acid mono-2-(methacryloyloxy)ethyl ester, ethoxylated castor oil glycolate, polyoxyethylene lauryl ether, sodium benzenesulfonate, sodium riboflavin phosphate, polyethylene glycol, stearic acid, butyl stearate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium dodecylsulfonate or sodium tetradecylsulfonate.

[0024] In some of these embodiments, the solvent in the coating agent solution includes at least one of water, methanol, ethanol, acetone, N-methylpyrrolidone, ethylene glycol, glycerol, pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, or N,N-diethylformamide.

[0025] In some of these embodiments, the coating agent in the coating agent solution further includes a metal compound.

[0026] In some of these embodiments, the metal compound includes at least one of Al2O3, TiO2, LiPO3, LATP, LLZO, LLTO, AlPO4, or Zr3(PO4)4.

[0027] In some of these embodiments, the mass ratio of the metal compound to the organic compound containing an electron-rich group is (0-1):1.

[0028] In some of these embodiments, the thickness of the coating layer is 5 nm to 20 nm.

[0029] In some of these embodiments, the mass ratio of the coating agent to the positive electrode material of the lithium-ion battery is (0.5%-5%):1.

[0030] In some of these embodiments, the reaction is carried out under the conditions of heating and stirring, and the heating temperature is 50°C to 90°C.

[0031] In some of these embodiments, the rotation speed of the stirring is 200 to 1000 rpm.

[0032] In some of these embodiments, after the reaction and before the sintering, it further includes the steps of washing, filtering, and drying carried out in sequence.

[0033] In some of these embodiments, the atmosphere during sintering includes at least one of air or oxygen.

[0034] In some of these embodiments, the sintering temperature is 400°C to 700°C, and the sintering time is 4 h to 10 h.

[0035] According to the third aspect of the present application, the present application provides a positive electrode sheet, which includes the aforementioned lithium-ion battery positive electrode composite material or the lithium-ion battery positive electrode composite material prepared according to the aforementioned preparation method.

[0036] According to the fourth aspect of the present application, the present application provides a battery, which includes the aforementioned lithium-ion battery positive electrode composite material, or includes the lithium-ion battery positive electrode composite material prepared according to the aforementioned preparation method, or includes the aforementioned positive electrode sheet.

[0037] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0038] In the embodiment of the present application, the provided lithium-ion battery positive composite material includes a lithium-ion battery positive electrode material and a coating layer coated on the surface of the lithium-ion battery positive electrode material; wherein, the coating agent for forming the coating layer includes an organic compound containing an electron-rich group, and this electron-rich group is suitable for binding to the lithium (Li) element or non-Li metal element in the lithium-ion battery positive electrode material through an ionic bond. Thus, by in-situ coating an organic compound with an electron-rich group on the surface of the positive electrode material, the Li-X or M-X formed by the electron-rich group (X) of the coating layer and the residual lithium or other metal cations (non-Li metal element, M) on the surface of the positive electrode has a strong binding energy, which can avoid the shedding and coating defects of the coating layer and improve the binding strength between the positive electrode material and the coating layer. In addition, the electron-rich group (X) reacts with the residual lithium on the surface of the positive electrode to generate a stable Li-X ionic bond, which can improve the ionic conductivity and the stability of surface oxygen. At the same time, the organic compound containing an electron-rich group has a carbon chain, and the high conductivity of the carbon chain in this organic compound is conducive to the rapid transport of electrons and charge transfer, thereby improving the rate performance.

[0039] In a preferred embodiment of the present application, the coating layer further contains a metal compound. For the metal compound-organic compound composite-coated positive electrode material, the lithium ions on the surface of the positive electrode material at the interface bind to the anions of the metal compound or the electron-rich groups of the organic compound, and at the same time, the cations of the metal compound can also bind to the electron-rich groups of the organic compound, which can also avoid the shedding and coating defects of the composite coating layer, and further improve the structural stability and electrochemical performance of the positive composite material.

[0040] The additional aspects and advantages of the present application will be partially given in the following description, partially become obvious from the following description, or be understood through the practice of the present invention. Description of the Drawings

[0041] Figure 1 Shown is the SEM image (scanning electron microscope image) of the lithium-ion battery positive composite material provided in Example 1 of the present invention.

[0042] Figure 2 Shown is the EDS image (energy dispersive X-ray spectroscopy image) of the lithium-ion battery positive composite material provided in Example 1 of the present invention.

[0043] Figure 3 Shown is the SEM image of the lithium-ion battery positive composite material provided in Example 2 of the present invention. Detailed Embodiments

[0044] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and not to limit the scope of the present application.

[0045] The endpoints and any values disclosed in this text are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values and individual point values of each range, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this text.

[0046] If there is no special instruction, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions.

[0047] If there is no special instruction, all technical features and optional technical features of the present application can be combined with each other to form new technical solutions.

[0048] If there is no special instruction, all steps of the present application can be carried out sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method can include steps (a) and (b) carried out sequentially, or can also include steps (b) and (a) carried out sequentially. For example, it is mentioned that the method may further include step (c), which means that step (c) can be added to the method in any order. For example, the method can include steps (a), (b) and (c), or can also include steps (a), (c) and (b), or can also include steps (c), (a) and (b), etc.

[0049] If there is no special instruction, the "including" and "comprising" mentioned in the present application mean open-ended, and can also be closed-ended. For example, the "including" and "comprising" can mean that other components not listed can also be included or comprised, or can only include or comprise the listed components.

[0050] As analyzed in the background art of the present application, coating and modifying the cathode material can play roles such as physically blocking the material and the electrolyte, passivating the surface of the cathode material, and inhibiting side reactions with the electrolyte. In the related art, on the one hand, the currently commonly used coating reagents are mainly electrochemically inert metal oxides (such as Al2O3, MgO, TiO2, etc.) and fast ion conductor solid electrolytes (such as LATP, LLZO, etc.). However, the coating layers of these substances are easily corroded and damaged by the electrolyte during the cycling process, and cannot play a lasting protective role for the cathode material matrix. After long cycling, a passivation layer that is not easy to conduct electrons and ions will also be generated on the surface of the cathode material, resulting in rapid capacity decay.

[0051] On the other hand, the currently commonly used coating materials can be divided into two categories: inorganic materials and organic materials. Among them, inorganic materials mainly include metal compounds such as phosphates, solid electrolytes, and electrode materials. These substances can improve ionic conductivity, prevent direct contact between the material and the electrolyte, and inhibit interfacial side reactions. However, there may also be problems such as low electronic conductivity and large interfacial charge transfer resistance. Organic materials mainly include conductive carbon and conductive polymers. These substances can form a coating layer with high electronic conductivity on the surface of the material, improve the mechanical strength of the material, and reduce cracks generated during charge and discharge due to volume changes. However, it is difficult to synthesize a uniform coating layer during the preparation process, and there is also a problem that the surface coating layer is prone to peeling off. In related technologies, in order to simultaneously improve the ionic and electronic conductivities of the cathode material, the advantages of two coating materials (inorganic materials and organic materials) are combined to form a double coating layer on the cathode surface. However, the double coating process in the prior art is complex, it is difficult to control the thickness and uniformity of the coating layer, and the bonding strength between the coating layers is also uncertain.

[0052] In view of the deficiencies in the prior art, through a large amount of research and practice, the inventors of the present application have been able to propose the technical solution of the present invention, providing a composite cathode material for a lithium-ion battery, a preparation method of the composite cathode material for a lithium-ion battery, a cathode sheet and a battery including the composite cathode material for a lithium-ion battery. The technical solution, its implementation process, principle, etc. will be further explained below.

[0053] In some embodiments, the present application provides a composite cathode material for a lithium-ion battery, which includes a cathode material for a lithium-ion battery and a coating layer coated on at least a part of the surface of the cathode material for a lithium-ion battery;

[0054] The coating agent for forming the coating layer includes an organic substance containing an electron-rich group, where the electron-rich group includes at least one of -OH, -COO - , -F, -Cl, -Br, -I, -SO4 or -SO3; the electron-rich group is suitable for binding to the Li element or non-Li metal element in the cathode material for a lithium-ion battery through an ionic bond.

[0055] The composite cathode material provided by the present application is applicable to a lithium-ion battery, so it can also be called a composite cathode material for a lithium-ion battery. The composite cathode material has a core-shell structure, that is, the composite cathode material has a coating layer, and the composite cathode material with the coating layer has a core-shell structure. The core (inner core) is the cathode material, which can be a cathode material for a lithium-ion battery, and the shell (outer shell or shell layer) is the coating layer. In the present application, a coating layer is formed on the surface of the inner core cathode material for a lithium-ion battery. The inner core cathode material for a lithium-ion battery contains lithium (Li) element and can also contain non-Li metal elements; the raw material coating agent for forming the coating layer can include an organic substance containing an electron-rich group.

[0056] It should be noted that in this application, the term "coating" is not limited to direct coating, but also includes indirect coating. For example, when the coating layer coats the core lithium-ion battery cathode material, there may be no other structure between the coating layer and the outer surface of the core lithium-ion battery cathode material, or there may be one or more other structures between the coating layer and the outer surface of the core lithium-ion battery cathode material. Preferably, there is no other structure between the coating layer and the outer surface of the core lithium-ion battery cathode material.

[0057] The above-mentioned coating layer can be formed on at least part of the surface of the core lithium-ion battery cathode material, which can play a role in protecting or improving the core lithium-ion battery cathode material, and can also play a role in improving the overall structural stability of the cathode composite material. The coating layer is formed or coated on at least part of the surface of the core lithium-ion battery cathode material means that the coating layer can completely encapsulate the core lithium-ion battery cathode material within the coating layer, or it can also be that the coating layer only coats a part of the outer surface of the core lithium-ion battery cathode material; that is, the coating layer can completely coat the core lithium-ion battery cathode material, or it can coat a part of the surface of the core lithium-ion battery cathode material, preferably complete coating.

[0058] In this application, the provided lithium-ion battery cathode composite material can be a cathode composite material with a core-shell structure obtained by sintering the cathode material modified by a coating agent. Among them, the presence of the coating layer can prevent the contact between the core and the electrolyte, alleviate the side reaction between the core and the electrolyte, improve the surface stability of the cathode material, and thus facilitate the improvement of the overall structural stability and cycle stability of the lithium-ion battery cathode composite material, and further improve the cycle stability and first Coulomb efficiency of the lithium-ion battery cathode composite material.

[0059] In particular, in this application, an electron-rich group organic substance is in-situ coated on the cathode material matrix to inhibit the interfacial side reaction with the electrolyte and improve the cycle stability. The coating agent in this application includes an organic substance containing an electron-rich group, and the electron-rich group can be denoted as X, and the X can be selected from any one or a combination of at least two of -OH, -COO - 、-F、-Cl、-Br、-I、-SO4 or -SO3. These electron-rich groups can provide a certain amount of electrons to other atoms or groups, which is beneficial to improving the stability of the cathode composite material and further enhancing the electrochemical performance of the cathode composite material. Specifically:

[0060] (1) In this application, the polar electron-rich group X in the coating agent reacts with the residual lithium on the surface of the cathode material or other metal cations in the cathode material to form stable Li-X ionic bonds and / or M-X ionic bonds. Li-X or M-X has a strong binding energy, which can avoid the shedding of the coating layer and coating defects, and is beneficial to improving the overall and surface stability of the cathode composite material for lithium-ion batteries.

[0061] (2) One side of the polar electron-rich group X reacts with the residual lithium on the surface of the cathode material to form stable Li-X ionic bonds, which can improve ionic conductivity and the stability of surface oxygen.

[0062] (3) The side of the alkane with a smaller polarity can reduce the water sensitivity of the material, inhibit the contact between the cathode material and the electrolyte, and thus reduce the interfacial side reactions.

[0063] (4) Compared with the cathode material and inorganic substances, the high conductivity of the carbon chain (carbon group) in the organic substance containing an electron-rich group is beneficial to the rapid transport of electrons and charge transfer, thereby improving the rate performance of the cathode composite material.

[0064] (5) Using a coating agent of an organic substance containing an electron-rich group, the properties of the organic substance can improve the mechanical strength of the cathode composite material and reduce the cracks generated due to volume changes during charge and discharge.

[0065] Therefore, based on the above, compared with conventional conductive polymers or other polymer coating agents, there is a problem that the conductive polymer and the cathode material matrix are connected by intermolecular forces, and the binding stability of the coating layer is low. The electron-rich group X of the coating agent in this application forms Li-X ionic bonds with the lithium on the surface of the cathode material, has a stronger binding energy, can avoid the shedding of the coating layer and coating defects, is beneficial to improving the stability of the cathode composite material, and further improves the electrochemical properties such as the cycle stability and the first Coulomb efficiency of the cathode composite material.

[0066] In some preferred implementation methods, the coating agent further includes a metal compound. That is, the coating agent in this application can mainly consist of an organic substance containing an electron-rich group and a metal compound, which can make the coating layer of the prepared cathode composite material for lithium-ion batteries contain not only Li-X ionic bonds and / or M-X ionic bonds but also metal compounds.

[0067] Therefore, for the metal compound-organic composite coated cathode material, the lithium ions on the surface of the cathode material at the interface combine with the anions of the metal compound or the electron-rich groups of the organic substance, and at the same time, the cations of the metal compound can also combine with the electron-rich groups of the organic substance, which can also avoid the shedding of the composite coating layer and coating defects, and further improve the structural stability and electrochemical properties of the cathode composite material.

[0068] The inventor of the present invention has found through in-depth research that when the positive electrode composite material of the lithium-ion battery of the present application meets the above design conditions, if it also optionally meets one or several of the following conditions, the performance of the positive electrode composite material of the lithium-ion battery can be further improved.

[0069] In some embodiments, the organic substances containing electron-rich groups include, but are not limited to, ethyl fluoroacetate, methyl difluoroacetate, isopropyl trifluoroacetate, butyl fluoroacetate, tetradecyl fluoride, chlorotetradecane, bromotetradecane, tetradecanedioic acid, tetradecanol, sodium tetradecylsulfonate, isopropylsulfonyl chloride, sodium polystyrenesulfonate, dipropylene glycol butyl ether, polypropylene oxide, sodium polyacrylate, methoxypolyethylene glycol, brominated epoxy resin, brominated polystyrene, 5-sulfosalicylic acid, sodium sulfosalicylate, maleic acid mono-2-(methacryloyloxy)ethyl ester, ethoxylated castor oil glycolate, polyoxyethylene lauryl ether, sodium benzenesulfonate, sodium riboflavin phosphate, polyethylene glycol, stearic acid, butyl stearate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium dodecylsulfonate or sodium tetradecylsulfonate, or any combination of at least two of them.

[0070] The above organic substances such as ethyl fluoroacetate, methyl difluoroacetate, sodium dodecylsulfonate, sodium tetradecylsulfonate, etc. all contain electron-rich groups, such as containing one or more of -OH, -COO - , -F, -Cl, -Br, -I, -SO4 or -SO3. By selecting the above several organic substances and using the electron-rich groups contained therein, the bonding strength between the positive electrode material and the coating layer can be improved, and the structural stability and electrochemical performance of the positive electrode composite material can be enhanced.

[0071] In some embodiments, the metal compounds include, but are not limited to, any one or a mixture of at least two of Al2O3, TiO2, LiPO3, LATP, LLZO, LLTO, AlPO4 or Zr3(PO4)4 in any proportion.

[0072] The metal compounds in the present application can be oxide solid electrolytes, such as oxide solid electrolytes such as LATP, LLZO, LLTO, etc., can also be ceramic oxides such as Al2O3, TiO2, etc., and can also be phosphorus-containing oxides, such as phosphorus-containing oxides such as LiPO3, AlPO4, Zr3(PO4)4, etc.

[0073] Thus, through the synergistic effect of the above metal compounds and the organic substances containing electron-rich groups, the amount of lithium ions bound to the surface of the positive electrode material can be increased, thereby further improving the bonding strength. The cations of the metal compounds can also be combined with the electron-rich groups of the organic substances to further prevent the shedding of the composite coating layer and coating defects.

[0074] In the present application, the core lithium-ion battery cathode material in the lithium-ion battery cathode composite material can adopt the conventional cathode materials used in the lithium-ion battery industry.

[0075] As an example, the lithium-ion battery cathode material contains Li element, other metal elements except lithium and oxygen element. The other metal elements except lithium, that is, non-Li metal elements, can be selected from elements such as transition metals, alkali metals or alkaline earth metals; in addition, the lithium-ion battery cathode material may also optionally include other non-metal elements such as phosphorus (P). For example, in some embodiments, the non-Li metal elements include, but are not limited to, one or a combination of at least two of Ni, Co, Fe, Mn, Zn, Mg, Cu, Al, Ti, Zr, Na or K. Preferably, in some embodiments, the non-Li metal elements are selected from one or more of Ni, Co, Fe, Mn, Al.

[0076] In some embodiments, the lithium-ion battery cathode material includes Li a M b P c O d , where 1≤a≤1.3, 0<b≤2, 0≤c≤1, 0<d≤4; M includes at least one of the non-Li metal elements. Preferably, M includes one or more of Ni, Co, Fe, Mn, Zn, Mg, Cu, Al, Ti, Zr, Na or K. More preferably, M includes one or more of Ni, Co, Fe, Mn, Al.

[0077] In the present application, the lithium-ion battery cathode material can be selected from one or a combination of at least two of lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminate, lithium nickel manganate, lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium cobalt phosphate or lithium-rich layered oxides and their doping modified materials. For the sake of brevity, the combinations within the above range will not be listed one by one.

[0078] As an example, the lithium-ion battery cathode material can be selected from Li a Ni b Co c Mn d Al e O2 (1≤a≤1.3, b + c + d + e = 1). For example, this material can be lithium nickel cobalt manganate or lithium nickel cobalt aluminate. Or, the lithium-ion battery cathode material can be selected from lithium cobaltate (LiCoO2). Or, the lithium-ion battery cathode material can be selected from lithium manganate (LiMn2O4). Or, the lithium-ion battery cathode material can be selected from LiM x Fe 1-x PO4 (0≤x≤0.5).

[0079] In addition, in other embodiments, the above-mentioned cathode materials for lithium-ion batteries are not limited to the several types listed above. Under the condition of meeting the basic requirements of the cathode active materials applicable to lithium batteries, etc., other types of cathode materials for lithium-ion batteries can also be used, which will not be described in detail one by one here.

[0080] In the present application, the cathode material for lithium-ion batteries can have various shape structures such as granular, blocky, nanowire / nanorod, etc., and the present application does not limit this.

[0081] Optionally, the average particle size of the cathode material for lithium-ion batteries is 0.5 μm to 20 μm. Further, the average particle size of the cathode material for lithium-ion batteries can be 1 μm to 15 μm. As an example, the average particle size of the cathode material for lithium-ion batteries can be any one of the point values of 0.5 μm, 1 μm, 2 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or the range value between any two of them.

[0082] By making the particle size of the cathode material for lithium-ion batteries within the above suitable range, the processing performance of the material can be improved, which is beneficial to processing, the effective compounding of the core cathode material and the coating agent can be ensured, and the comprehensive electrical performance of the cathode composite material for lithium-ion batteries can also be relatively good. In addition, using a core cathode material with a smaller particle size is beneficial to improving the first Coulomb efficiency of the material or improving the rate performance of the material.

[0083] In some embodiments, the thickness of the coating layer is 5 nm to 20 nm. As an example, the thickness of the coating layer can be any one of the point values of 5 nm, 10 nm, 15 nm, 20 nm or the range value between any two of them.

[0084] The thickness of the above coating layer can be adjusted according to the size of the core cathode material. A suitable thickness of the coating layer can not only ensure good processing performance of the cathode composite material, but also avoid the situation that too thick a thickness and too much coating material affect the timely release of active lithium, increase the battery impedance or affect the cycle performance of the battery cell, or can also avoid that too thin a thickness is not enough to effectively exert the modification effect of the coating layer, that is, it can avoid that too thin a thickness reduces the effect of the coating layer in improving the structural strength of the material.

[0085] Correspondingly, in some embodiments, the present application provides a preparation method for a cathode composite material for lithium-ion batteries, and this method includes the following steps:

[0086] Provide a cathode material solution for lithium-ion batteries and a coating agent solution respectively;

[0087] Mix the cathode material solution for lithium-ion batteries and the coating agent solution, and obtain a coated matrix material after reaction;

[0088] sintering the coated matrix material to obtain a lithium-ion battery positive electrode composite material;

[0089] The lithium-ion battery positive electrode composite material comprises a lithium-ion battery positive electrode material and a coating layer coated on at least a portion of the surface of the lithium-ion battery positive electrode material;

[0090] The coating agent in the coating agent solution includes organic matter containing electron-rich groups, wherein the electron-rich groups include -OH, -COO - , at least one of -F, -Cl, -Br, -I, -SO4 or -SO3; the electron-rich group is suitable for combining with the Li element or non-Li metal element in the positive electrode material of the lithium-ion battery through an ionic bond.

[0091] In the present invention, a coating agent solution can be provided first, and then the coating agent solution and the lithium ion battery positive electrode material solution are evenly mixed. After the reaction, a coating matrix material can be obtained. After the coating matrix material is sintered, a coating layer can be formed on the surface of the lithium ion battery positive electrode material to obtain a lithium ion battery positive electrode composite material.

[0092] The preparation method provided by the embodiment of the present invention has simple process, convenient operation, strong feasibility, low energy consumption, and is easy to industrialize; the method can prepare a lithium-ion battery positive electrode composite material with good structural stability and excellent electrochemical performance.

[0093] It should be understood that all the features and advantages described above for the “lithium-ion battery positive electrode composite material” are also applicable to the “method for preparing the lithium-ion battery positive electrode composite material” and will not be described in detail here.

[0094] In some specific embodiments, the method for preparing the lithium-ion battery positive electrode composite material specifically comprises the following steps (a) to (b):

[0095] (a) Preparation of coating substrate material.

[0096] In some embodiments, in step (a), a coating agent solution is first provided, for example, the coating agent is added to a solvent and dispersed evenly to obtain a coating agent solution; then the lithium-ion battery positive electrode material is added to the solvent to obtain a positive electrode material solution, and during the heating and stirring process, the coating agent solution is slowly added to the positive electrode material solution. After sufficient reaction, washing, filtering and drying are performed to obtain a coated matrix material.

[0097] In step (a), the reaction is carried out under heating and stirring conditions, and the heating temperature (reaction temperature) is 50° C. to 90° C. As an example, the reaction temperature can be 50° C., 60° C., 70° C., 80° C., 90° C., etc., and of course it can also be other values within the above range, which is not limited here.

[0098] Optionally, the stirring speed is 200 to 1000 rpm. As an example, the stirring speed can be 200 rpm, 300 rpm, 500 rpm, 600 rpm, 800 rpm, 1000 rpm, etc. Of course, it can also be other values within the above range, which is not limited herein.

[0099] Optionally, the reaction time can be 2 h to 8 h, for example, it can be 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, etc.

[0100] In step (a), after sufficient reaction, the material obtained after the reaction needs to be washed, filtered, and dried in sequence. The filtration can be carried out by suction filtration, which can improve the purity of the product and the yield.

[0101] It should be noted that the specific operating conditions for the above washing, suction filtration, and drying can be selected and set according to actual needs, which is not limited herein.

[0102] In step (a), the lithium-ion battery cathode material in the lithium-ion battery cathode material solution includes Li a M b P c O d , where M includes at least one of non-Li metal elements, 1 ≤ a ≤ 1.3, 0 < b ≤ 2, 0 ≤ c ≤ 1, 0 < d ≤ 4. Among them, M includes at least one of Ni, Co, Fe, Mn, Zn, Mg, Cu, Al, Ti, Zr, Na, or K.

[0103] In step (a), the solvent in the lithium-ion battery cathode material solution includes, but is not limited to, at least one of water, methanol, ethanol, acetone, N-methylpyrrolidone, ethylene glycol, glycerol, pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, or N,N-diethylformamide; of course, it is not limited thereto, as long as it can be used to disperse or dissolve the cathode material and does not limit the purpose of this application.

[0104] In step (a), the coating agent includes an organic compound containing an electron-rich group, and the organic compound containing an electron-rich group includes at least one of ethyl fluoroacetate, methyl difluoroacetate, isopropyl trifluoroacetate, butyl fluoroacetate, tetradecyl fluoride, chlorotetradecane, bromotetradecane, tetradecanedioic acid, tetradecanol, sodium tetradecylsulfonate, isopropylsulfonyl chloride, sodium polystyrenesulfonate, dipropylene glycol butyl ether, polypropylene oxide, sodium polyacrylate, methoxypolyethylene glycol, brominated epoxy resin, brominated polystyrene, 5-sulfosalicylic acid, sodium sulfosalicylate, mono-2-(methacryloyloxy)ethyl maleate, ethoxylated castor oil glycolic acid, polyoxyethylene lauryl ether, sodium benzenesulfonate, sodium riboflavin phosphate, polyethylene glycol, stearic acid, butyl stearate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium dodecylsulfonate or sodium tetradecylsulfonate.

[0105] In step (a), the coating agent further includes a metal compound. The metal compound includes at least one of Al2O3, TiO2, LiPO3, LATP, LLZO, LLTO, AlPO4 or Zr3(PO4)4.

[0106] In step (a), the solvent in the coating agent solution includes, but is not limited to, at least one of water, methanol, ethanol, acetone, N-methylpyrrolidone, ethylene glycol, glycerol, pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or N,N-diethylformamide.

[0107] In step (a), in the coating agent, the mass ratio of the metal compound to the organic compound containing an electron-rich group is (0-1):1. Preferably, the mass ratio of the metal compound to the organic compound containing an electron-rich group is (0.01-1):1. As an example, the mass ratio of the metal compound to the organic compound containing an electron-rich group can be 0.01:1, 0.05:1, 0.1:1, 0.5:1, 0.6:1, 0.8:1, 1:1, etc.

[0108] In step (a), the mass ratio of the coating agent to the positive electrode material of the lithium ion battery is (0.5%-5%):1. As an example, the mass ratio of the coating agent to the positive electrode material of the lithium ion battery can be 0.5%:1, 0.8%:1, 1%:1, 2%:1, 3%:1, 4%:1, 5%:1, etc. Of course, it can also be other values within the above range, which are not limited here.

[0109] (b) Sintering treatment.

[0110] In step (b), sintering the coated matrix material can obtain the positive electrode composite material of the lithium ion battery. For example, sintering the powdered coated matrix material at high temperature in a muffle furnace, and pulverizing and sieving after cooling to obtain the positive electrode composite material of the lithium ion battery.

[0111] In some embodiments, in step (b), the atmosphere during sintering includes at least one of air or oxygen. For example, the atmosphere during sintering can be air, or can be oxygen.

[0112] In some embodiments, in step (b), the sintering temperature is 400°C to 700°C, and the sintering time is 4h to 10h. As an example, the sintering temperature can be any point value among 400°C, 500°C, 600°C, 700°C or the range value between any two of them; the sintering time can be any point value among 4h, 5h, 6h, 7h, 8h, 10h or the range value between any two of them.

[0113] In some embodiments, the thickness of the coating layer is 5nm to 20nm.

[0114] Thus, by controlling the conditions such as the sintering temperature and time in step (b) within the above ranges, it helps to improve the micro-morphology, helps to obtain a lithium-ion battery cathode composite material with excellent performance, and can further improve the electrochemical performance of the lithium-ion battery cathode composite material product.

[0115] The preparation method of the lithium-ion battery cathode composite material provided in the above embodiments of the present invention has a simple process, strong operability, and is suitable for large-scale production.

[0116] In some embodiments, the present application provides a positive electrode sheet, which includes a current collector and a positive electrode active material layer provided on the surface of the current collector; the positive electrode active material layer includes the aforementioned lithium-ion battery cathode composite material or the lithium-ion battery cathode composite material prepared according to the aforementioned preparation method.

[0117] The positive electrode sheet includes the above lithium-ion battery cathode composite material provided in the embodiments of the present application. Therefore, the positive electrode sheet also has the characteristic of excellent electrochemical performance.

[0118] The present application does not particularly limit the material of the current collector in the positive electrode sheet, as long as the purpose of the present application can be achieved, and it can be selected according to actual needs. For example, in some embodiments, the positive electrode current collector can include aluminum foil, aluminum alloy foil, carbon-coated aluminum foil, etc. Of course, in other embodiments, a composite current collector (such as a composite current collector formed by a metal and a polymer) can also be used.

[0119] In some embodiments, the positive electrode active material layer further includes a conductive agent and a binder.

[0120] In the embodiments of the present application, there is no particular limitation on the types of conductive agents and binders in the positive electrode active material layer, as long as the object of the present application can be achieved. For example, in some embodiments, the binder may include, but is not limited to, one or more of polyacrylate, polyimide, polyvinyl alcohol, polyamide, polyamideimide, polyvinylidene fluoride, styrene-butadiene copolymer (styrene-butadiene rubber), polytetrafluoroethylene, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, or sodium hydroxymethyl cellulose. The conductive agent may include, but is not limited to, at least one of conductive carbon black (such as acetylene black, Ketjen black), carbon nanotubes (CNTs), carbon fibers, graphene, etc. The above carbon nanotubes may be single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0121] Optionally, in the positive electrode active material layer, the mass ratio of the positive electrode composite material, conductive agent, and binder of the lithium-ion battery is (80-98):(1-10):(1-10).

[0122] The present application has no particular limitation on the preparation method of the positive electrode sheet, and a preparation method well-known in the art can be selected as long as the object of the present application can be achieved. For example, the preparation method of the positive electrode sheet includes, but is not limited to, the following steps: dispersing the positive electrode composite material, conductive agent, and binder of the lithium-ion battery in an N-methylpyrrolidone (NMP) solvent and mixing to form a uniform positive electrode slurry, coating the positive electrode slurry on the positive electrode current collector, and obtaining the positive electrode sheet through processes such as drying, cold pressing, and slitting.

[0123] In some embodiments, the embodiments of the present application provide a battery, which includes the aforementioned positive electrode sheet and a negative electrode sheet.

[0124] This battery includes the above-mentioned positive electrode composite material for lithium-ion batteries provided by the embodiments of the present application. Therefore, this battery, such as a lithium-ion secondary battery, also has the characteristic of excellent electrochemical performance.

[0125] The above battery can be a secondary battery or a primary battery, preferably a secondary battery. For example, the above battery can be a lithium-ion secondary battery, a lithium primary battery, etc., but is not limited thereto. The battery structure of the present application includes, but is not limited to, a soft-pack lithium-ion battery, a square hard-shell battery, a cylindrical hard-shell battery, etc.

[0126] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode material. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is provided on any one or both of the two opposite surfaces of the negative electrode current collector.

[0127] In this embodiment, for the negative electrode sheet, the specific materials, structures, etc. of the negative electrode current collector and the negative electrode active material layer are not limited, and the structures and components of the negative electrode sheet that can be used in secondary batteries and are well-known to those skilled in the art can be selected.

[0128] In some embodiments, the battery further includes an electrolyte and a separator.

[0129] The above electrolyte can be an electrolytic solution, and the electrolytic solution that can be used in the embodiments of the present application can be an electrolytic solution known in the prior art. The specific type and structure of the electrolytic solution can be the type of electrolytic solution that is well-known to those skilled in the art and can be used in secondary batteries.

[0130] The present application does not particularly limit the type of the separator, and any well-known porous separator with good chemical stability and mechanical stability can be selected. As an example, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride.

[0131] Hereinafter, the implementation manners of the present application will be described. The implementation manners described below are exemplary and are only used to explain the present application and should not be construed as a limitation to the present application. For those implementation manners where specific technologies or conditions are not specified, the technologies or conditions described in the literature in the art or according to the product specifications shall be followed. For the reagents, materials, or instruments whose manufacturers are not specified, they are all conventional products that can be obtained through commercial purchase.

[0132] Example 1

[0133] The preparation of the lithium-ion battery positive composite material includes the following steps:

[0134] According to the mass ratio LiNi 0.6 Co 0.2 Mn 0.2 O2:C 14 H 29 F = 1:0.01, respectively weigh the corresponding lithium-ion battery positive electrode material and tetradecyl fluoride, and dissolve them in deionized water and disperse them evenly to obtain a lithium-ion battery positive electrode material solution and a coating agent solution respectively; slowly add the tetradecyl fluoride solution (coating agent solution) to the lithium-ion battery positive electrode material solution under stirring at 400 rpm while heating at 80 °C, wash, filter, and dry after reacting fully for 6 h to obtain a coated matrix material;

[0135] Place the above coated matrix material in a muffle furnace and sinter it at 500 °C for 6 h in an air atmosphere, and sieve it after cooling to obtain the lithium-ion battery positive composite material.

[0136] The SEM diagram of the lithium-ion battery positive composite material prepared in Example 1 is as Figure 1As shown, the EDS diagram (energy dispersive X-ray spectrogram) of the lithium-ion battery cathode composite material prepared in Example 1 is as Figure 2 shown, from Figure 1 and Figure 2 it can be seen the morphology and element distribution of the prepared lithium-ion battery cathode composite material. It can be known that the particle surface is smooth and clean, and no small impurity particles are observed. The F and C elements are evenly distributed on the surface.

[0137] Example 2

[0138] The preparation of the lithium-ion battery cathode composite material includes the following steps:

[0139] According to the mass ratio LiNi 0.6 Co 0.2 Mn 0.2 O2:Al2O3:C 14 H 29 NaO3S = 1:0.005:0.01, respectively weigh the corresponding lithium-ion battery cathode material, Al2O3 and sodium tetradecylsulfonate, and dissolve them separately in deionized water and disperse evenly to obtain the lithium-ion battery cathode material solution and the coating agent solution; at 80 °C, heat and stir at 400 rpm, and slowly add the Al2O3 and sodium tetradecylsulfonate solution (coating agent solution) to the lithium-ion battery cathode material solution. After fully reacting for 6 h, wash, filter, and dry to obtain the coated matrix material;

[0140] Place the above-mentioned coated matrix material in a muffle furnace and sinter at 500 °C for 6 h in an air atmosphere. After cooling, sieve to obtain the lithium-ion battery cathode composite material.

[0141] The SEM diagram of the lithium-ion battery cathode composite material prepared in Example 2 is as Figure 3 shown, from Figure 3 it can be seen the morphology of the prepared lithium-ion battery cathode composite material. It can be known that the particle surface is smooth and clean, and no small impurity particles are observed.

[0142] Example 3

[0143] The preparation of the lithium-ion battery cathode composite material includes the following steps:

[0144] According to the mass ratio LiNi 0.6 Co 0.2 Mn 0.2 O2:Al2O3:C 14 H 29Weigh the corresponding lithium-ion battery cathode material, Al2O3, and sodium tetradecylsulfonate according to the mass ratio of LiNiCoMnO2:Al2O3:C12H25NaO3S = 1:0.002:0.01, and dissolve them separately in deionized water and disperse them evenly to obtain the lithium-ion battery cathode material solution and the coating agent solution respectively; slowly add the Al2O3 and sodium tetradecylsulfonate solution (coating agent solution) to the lithium-ion battery cathode material solution under stirring at 500 rpm and heating at 90 °C, wash, filter, and dry after fully reacting for 5 h to obtain the coated matrix material;

[0145] Put the above-mentioned coated matrix material into a muffle furnace and sinter it at 450 °C for 6 h in an air atmosphere, and sieve it after cooling to obtain the lithium-ion battery cathode composite material.

[0146] Example 4

[0147] The preparation of the lithium-ion battery cathode composite material includes the following steps:

[0148] According to the mass ratio of LiNi 0.6 Co 0.2 Mn 0.2 O2:Al2O3:C 14 H 29 Weigh the corresponding lithium-ion battery cathode material, Al2O3, and sodium tetradecylsulfonate according to the mass ratio of LiNiCoMnO2:Al2O3:C12H25NaO3S = 1:0.01:0.01, and dissolve them separately in deionized water and disperse them evenly to obtain the lithium-ion battery cathode material solution and the coating agent solution respectively; slowly add the Al2O3 and sodium tetradecylsulfonate solution (coating agent solution) to the lithium-ion battery cathode material solution under stirring at 400 rpm and heating at 80 °C, wash, filter, and dry after fully reacting for 6 h to obtain the coated matrix material;

[0149] Put the above-mentioned coated matrix material into a muffle furnace and sinter it at 500 °C for 6 h in an air atmosphere, and sieve it after cooling to obtain the lithium-ion battery cathode composite material.

[0150] Example 5

[0151] The preparation of the lithium-ion battery cathode composite material includes the following steps:

[0152] According to the mass ratio of LiNi 0.6 Co 0.2 Mn 0.2 O2:TiO2:C 14 H 29Weigh the corresponding lithium-ion battery cathode material, TiO₂, and tetradecyl bromide at a mass ratio of Br = 1:0.005:0.01, and dissolve them separately in deionized water and disperse evenly to obtain a lithium-ion battery cathode material solution and a coating agent solution respectively; slowly add the TiO₂ and tetradecyl bromide solution (coating agent solution) to the lithium-ion battery cathode material solution under stirring at 500 rpm and heating at 70 °C, wash, filter, and dry after reacting fully for 6 h to obtain a coated matrix material;

[0153] Place the above coated matrix material in a muffle furnace and sinter it at 600 °C for 6 h in an air atmosphere, and sieve it after cooling to obtain a lithium-ion battery cathode composite material.

[0154] Example 6

[0155] The preparation of the lithium-ion battery cathode composite material includes the following steps:

[0156] According to the mass ratio LiNi 0.6 Co 0.2 Mn 0.2 O₂:LATP:C 14 H 29 Cl = 1:0.005:0.01, weigh the corresponding lithium-ion battery cathode material, LATP, and tetradecyl chloride respectively, and dissolve them separately in deionized water and disperse evenly to obtain a lithium-ion battery cathode material solution and a coating agent solution respectively; slowly add the LATP and tetradecyl chloride solution (coating agent solution) to the lithium-ion battery cathode material solution under stirring at 500 rpm and heating at 70 °C, wash, filter, and dry after reacting fully for 6 h to obtain a coated matrix material;

[0157] Place the above coated matrix material in a muffle furnace and sinter it at 600 °C for 6 h in an air atmosphere, and sieve it after cooling to obtain a lithium-ion battery cathode composite material.

[0158] Example 7

[0159] The preparation of the lithium-ion battery cathode composite material includes the following steps:

[0160] According to the mass ratio LiNi 0.6 Co 0.2 Mn 0.2 O₂:C 14 H 29 F = 1:0.05, weigh the corresponding lithium-ion battery cathode material and tetradecyl fluoride respectively, and dissolve them separately in deionized water and disperse evenly to obtain a lithium-ion battery cathode material solution and a coating agent solution respectively; slowly add the tetradecyl fluoride solution (coating agent solution) to the lithium-ion battery cathode material solution under stirring at 400 rpm and heating at 80 °C, wash, filter, and dry after reacting fully for 6 h to obtain a coated matrix material;

[0161] The above-coated matrix material was placed in a muffle furnace and sintered at 500 °C for 6 h in an air atmosphere. After cooling, it was sieved to obtain the lithium-ion battery cathode composite material.

[0162] Comparative Example 1

[0163] The preparation of the lithium-ion battery cathode composite material includes the following steps:

[0164] According to the mass ratio of LiNi 0.6 Co 0.2 Mn 0.2 O2:CH3(CH2) 12 CH3:LiF = 1:0.00917:0.00120, respectively weigh the corresponding lithium-ion battery cathode material, tetradecane, and lithium fluoride, and dissolve them in deionized water and disperse them evenly to obtain the lithium-ion battery cathode material solution and the coating agent solution respectively; the coating agent solution was slowly added to the lithium-ion battery cathode material solution with stirring at 400 rpm while heating at 80 °C. After reacting for 6 h, it was washed, filtered, and dried to obtain the coated matrix material;

[0165] The above-coated matrix material was placed in a muffle furnace and sintered at 500 °C for 6 h in an air atmosphere. After cooling, it was sieved to obtain the lithium-ion battery cathode composite material.

[0166] In Comparative Example 1, the coating agent used was CH3(CH2) 12 CH3 and LiF.

[0167] Comparative Example 2

[0168] The preparation of the lithium-ion battery cathode composite material includes the following steps:

[0169] According to the mass ratio of LiNi 0.6 Co 0.2 Mn 0.2 O2:CH3(CH2) 12 CH3 = 1:0.01, respectively weigh the corresponding lithium-ion battery cathode material and tetradecane, and dissolve them in deionized water and disperse them evenly to obtain the lithium-ion battery cathode material solution and the coating agent solution respectively; the coating agent solution was slowly added to the lithium-ion battery cathode material solution with stirring at 400 rpm while heating at 80 °C. After reacting for 6 h, it was washed, filtered, and dried to obtain the coated matrix material;

[0170] The above-coated matrix material was placed in a muffle furnace and sintered at 500 °C for 6 h in an air atmosphere. After cooling, it was sieved to obtain the lithium-ion battery cathode composite material.

[0171] In Comparative Example 2, the coating agent used was CH3(CH2) 12 CH3.

[0172] Comparative Example 3

[0173] Preparation of the composite cathode material for lithium-ion batteries, comprising the following steps:

[0174] According to a mass ratio of LiNi 0.6 Co 0.2 Mn 0.2 O2:CH3(CH2) 12 CH3:LiF = 1:0.00137, respectively weigh the corresponding cathode materials for lithium-ion batteries and lithium fluoride, and dissolve them separately in deionized water and disperse them evenly to obtain a cathode material solution for lithium-ion batteries and a coating agent solution; slowly add the coating agent solution to the cathode material solution for lithium-ion batteries under stirring at 400 rpm while heating at 80 °C, after fully reacting for 6 h, wash, filter, and dry to obtain a coated matrix material;

[0175] Place the above-mentioned coated matrix material in a muffle furnace and sinter at 500 °C for 6 h in an air atmosphere, and after cooling, sieve to obtain the composite cathode material for lithium-ion batteries.

[0176] In Comparative Example 1, the coating agent used is LiF.

[0177] Performance testing

[0178] Respectively prepare the composite cathode materials for lithium-ion batteries obtained in the above-mentioned examples and comparative examples into batteries, and conduct performance testing on the batteries, specifically including:

[0179] 1. Preparation of the battery

[0180] (1) Preparation of the positive electrode sheet: Mix the above-mentioned composite cathode material for lithium-ion batteries, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride (PVDF) according to a mass ratio of 93:5:2, add the solvent NMP and stir to form a uniformly mixed and stable positive electrode slurry; uniformly coat the positive electrode slurry on the pretreated aluminum foil, and after drying, rolling, and cutting, obtain a positive electrode sheet, and the positive electrode sheet is a circular positive electrode sheet with a diameter of 14 mm.

[0181] (2) Preparation of the negative electrode sheet: Use a metal lithium sheet with a diameter of 14 mm and a thickness of 0.2 mm as the negative electrode sheet.

[0182] (3) Preparation of the electrolyte: Mix ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) according to a volume ratio of 1:1:1 to obtain an organic solvent, and then add 3 wt% of vinylene carbonate (FEC) and the solute LiPF6 to the organic solvent, dissolve and mix evenly to obtain the electrolyte; the concentration of LiPF6 is 1.0 mol / L.

[0183] (4) Selection of the separator: A polypropylene film with a thickness of 13 μm is selected as the separator.

[0184] (5) Assembly of the battery: Arrange the positive electrode sheet, separator, and negative electrode sheet in sequence. The lamination method is selected for the assembly. After processes such as baking, electrolyte injection, formation, aging, and grading, a CR2032 button battery is assembled in a glove box filled with high-purity argon.

[0185] 2. Electrochemical performance tests are carried out on the assembled battery, including:

[0186] (1) Tests on the first charge specific capacity, first discharge specific capacity, and first efficiency (first Coulombic efficiency):

[0187] Under the constant temperature condition of 25 °C, charge at a constant current of 0.1C to 4.3V, and record the charging capacity at this time as the first charging capacity; after standing, discharge at a constant current of 0.1C to 2V, and record the discharge capacity at this time as the first discharge capacity; the first Coulombic efficiency = first discharge specific capacity / first charging specific capacity * 100%.

[0188] (2) Tests on the 1C discharge specific capacity and cycle performance: Under the constant temperature condition of 25 °C, perform activation treatment (charge at a constant current of 0.1C to 4.3V, then discharge at a constant current of 0.1C to 2V, and repeat this process 2 cycles); charge at a constant current of 1C to 4.3V, and then discharge at a constant current of 1C to 2V. Record the discharge capacity at this time as the 1C discharge specific capacity, which is the first cycle; repeat this process until the 50th cycle, end the test, and record the discharge specific capacity of the 50th cycle. Then, the cycle performance = discharge specific capacity of the 50th cycle / discharge specific capacity of the first cycle * 100%.

[0189] The above test results are shown in Table 1.

[0190] Table 1 Performance test results of the batteries in each example and the comparison.

[0191]

[0192] It can be seen from the data in Table 1 that compared with Comparative Examples 1-3, the button batteries prepared with the lithium-ion battery positive composite materials provided in Examples 1-7 all have higher initial charge and discharge capacities, higher first inventory efficiency, and good cycle performance. This shows that compared with the common or existing materials on the market, the structural stability of the lithium-ion battery positive composite material prepared in the embodiments of the present invention has been significantly increased. Therefore, by utilizing the excellent structural stability of the lithium-ion battery positive composite material, the shedding and coating defects of the coating layer can be avoided, the rate performance can be improved, the contact between the material and the electrolyte can be inhibited, and the interfacial side reaction can be reduced, thereby facilitating the improvement of electrochemical performances such as the cycle stability of the material at 1C rate.

[0193] In addition, by comparing Comparative Example 1 and Example 1, it can be seen that since Comparative Example 1 uses CH3(CH2) 12 CH3 and LiF composite coating agent, the residual lithium on the surface of the cathode material is not consumed, resulting in lower capacity and cycling performance of the battery prepared therefrom. By comparing Comparative Example 2 and Example 1, it can be seen that since Comparative Example 2 uses CH3(CH2) 12 CH3 coating agent, neither the residual lithium on the surface is consumed nor a stable coating layer is formed, and its cycling performance is lower than that of Example 1 and Comparative Example 1. By comparing Comparative Example 3 and Example 1, it can be seen that since Comparative Example 3 uses LiF coating agent, neither the residual lithium on the surface is consumed nor a stable coating layer is formed, and its cycling performance is lower than that of Example 1 and Comparative Example 1.

[0194] The parts not described in detail in the present invention are well-known technologies to those skilled in the art.

[0195] The basic principles of the present invention have been described above in conjunction with specific embodiments. However, it should be noted that the advantages, advantages, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, advantages, effects, etc. are essential for each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitating understanding, rather than limitations. The above details do not limit the present invention to necessarily adopt the above specific details to implement.

[0196] It should be noted that the term "and / or" or " / " used herein is only a description of the association relationship of the associated objects, indicating that three relationships may exist. For example, A and / or B may mean: A exists alone, A and B exist simultaneously, and B exists alone. The singular forms of "a", "the" and "said" used in the embodiments of the present invention and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0197] In the specific embodiments and claims, the list of items connected by the terms "at least one of", "at least one of", "at least one kind of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0198] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A composite cathode material for a lithium-ion battery, characterized in that, The positive composite material of the lithium-ion battery includes a positive material of the lithium-ion battery and a coating layer coated on at least a part of the surface of the positive material of the lithium-ion battery; The coating agent used to form the coating layer includes an organic compound containing an electron-rich group, where the electron-rich group includes at least one of -OH, -COO - , -F, -Cl, -Br, -I, -SO4 or -SO3; The electron-rich group is suitable for binding with the Li element or non-Li metal element in the positive material of the lithium-ion battery through an ionic bond.

2. The cathode composite material for a lithium-ion battery according to claim 1, wherein The non-Li metal element includes at least one of Ni, Co, Fe, Mn, Zn, Mg, Cu, Al, Ti, Zr, Na or K; and / or, The organic compound containing an electron-rich group includes at least one of ethyl fluoroacetate, methyl difluoroacetate, isopropyl trifluoroacetate, butyl fluoroacetate, tetradecyl fluoride, chlorotetradecane, bromotetradecane, tetradecanedioic acid, tetradecanol, sodium tetradecylsulfonate, isopropylsulfonyl chloride, sodium polystyrenesulfonate, dipropylene glycol butyl ether, polypropylene oxide, sodium polyacrylate, methoxypolyethylene glycol, brominated epoxy resin, brominated polystyrene, 5-sulfosalicylic acid, sodium sulfosalicylate, maleic acid mono-2-(methacryloyloxy)ethyl ester, ethoxylated castor oil glycolate, polyoxyethylene lauryl ether, sodium benzenesulfonate, sodium riboflavin phosphate, polyethylene glycol, stearic acid, butyl stearate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium dodecylsulfonate or sodium tetradecylsulfonate.

3. The cathode composite material for a lithium-ion battery according to claim 1 or 2, characterized in that, The coating agent further includes a metal compound; Preferably, the metal compound includes at least one of Al2O3, TiO2, LiPO3, LATP, LLZO, LLTO, AlPO4 or Zr3(PO4)4; Preferably, the thickness of the coating layer is 5 nm to 20 nm.

4. A method for preparing a composite cathode material for a lithium-ion battery, characterized in that, Comprising the following steps: Providing a positive material solution of the lithium-ion battery and a coating agent solution respectively; Mixing the positive material solution of the lithium-ion battery and the coating agent solution, and obtaining a coated matrix material after reaction; Sintering the coated matrix material to obtain the positive composite material of the lithium-ion battery; The positive composite material of the lithium-ion battery includes a positive material of the lithium-ion battery and a coating layer coated on at least a part of the surface of the positive material of the lithium-ion battery; The coating agent in the coating agent solution includes an organic compound containing an electron-rich group, where the electron-rich group includes at least one of -OH, -COO - , -F, -Cl, -Br, -I, -SO4 or -SO3; The electron-rich group is suitable for binding with the Li element or non-Li metal element in the positive material of the lithium-ion battery through an ionic bond.

5. The preparation method of the lithium ion battery cathode composite material according to claim 4, wherein, The lithium-ion battery cathode material in the lithium-ion battery cathode material solution includes Li a M b P c O d , where M includes at least one of non-Li metal elements, 1 ≤ a ≤ 1.3, 0 < b ≤ 2, 0 ≤ c ≤ 1, 0 < d ≤ 4; Preferably, the M includes at least one of Ni, Co, Fe, Mn, Zn, Mg, Cu, Al, Ti, Zr, Na or K; Preferably, the solvent in the positive material solution of the lithium-ion battery includes at least one of water, methanol, ethanol, acetone, N-methylpyrrolidone, ethylene glycol, glycerol, pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or N,N-diethylformamide.

6. The preparation method of the lithium ion battery cathode composite material according to claim 4, characterized in that The organic compounds containing electron-rich groups include at least one of ethyl fluoroacetate, methyl difluoroacetate, isopropyl trifluoroacetate, butyl fluoroacetate, tetradecyl fluoride, chlorotetradecane, bromotetradecane, tetradecanedioic acid, tetradecanol, sodium tetradecylsulfonate, isopropylsulfonyl chloride, sodium polystyrenesulfonate, dipropylene glycol butyl ether, polypropylene oxide, sodium polyacrylate, methoxypolyethylene glycol, brominated epoxy resin, brominated polystyrene, 5-sulfosalicylic acid, sodium sulfosalicylate, mono-2-(methacryloyloxy)ethyl maleate, ethoxylated castor oil glycolate, polyoxyethylene lauryl ether, sodium benzenesulfonate, sodium riboflavin phosphate, polyethylene glycol, stearic acid, butyl stearate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium dodecylsulfonate or sodium tetradecylsulfonate; Preferably, the solvent in the coating agent solution includes at least one of water, methanol, ethanol, acetone, N-methylpyrrolidone, ethylene glycol, glycerol, pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or N,N-diethylformamide.

7. The preparation method of the composite cathode material for lithium ion batteries according to claim 6, characterized in that, The coating agent in the coating agent solution further includes a metal compound; Preferably, the metal compound includes at least one of Al2O3, TiO2, LiPO3, LATP, LLZO, LLTO, AlPO4 or Zr3(PO4)4; Preferably, the mass ratio of the metal compound to the organic compound containing an electron-rich group is (0-1):

1.

8. The preparation method of the composite cathode material for a lithium-ion battery according to any one of claims 4 to 7, characterized in that, The thickness of the coating layer is 5 nm to 20 nm; and / or The mass ratio of the coating agent to the positive electrode material of the lithium ion battery is (0.5%-5%):1; and / or The reaction is carried out under the conditions of heating and stirring, and the heating temperature is 50 °C to 90 °C; preferably, the stirring speed is 200 to 1000 rpm; preferably, after the reaction and before the sintering, the steps of washing, filtering and drying are further included in sequence; and / or The atmosphere during sintering includes at least one of air or oxygen; and / or The sintering temperature is 400 °C to 700 °C, and the sintering time is 4 h to 10 h.

9. A positive electrode sheet, characterized in that, The positive electrode sheet includes the lithium ion battery positive composite material according to any one of claims 1 to 3 or the lithium ion battery positive composite material prepared by the preparation method according to any one of claims 4 to 8.

10. A battery, characterized in that, The battery includes the lithium ion battery positive composite material according to any one of claims 1 to 3, or includes the lithium ion battery positive composite material prepared by the preparation method according to any one of claims 4 to 8, or includes the positive electrode sheet according to claim 9.

Citation Information

Cited By

  • Surface modified negative electrode material as well as preparation method and application thereof

    CN121123208A